Testing Financial Ratios on Business Values of Property and Real Estate Companies Listed in Indonesia Stock Exchange (IDX) - Muhammad Jalari; Agus Marimin (International Journal of Seocology, 2020)
This study aims to examine the financial ratios of profitability and solvency to the value of the property and real estate companies in the Indonesia Stock Exchange in the period 2008 - 2018. The data used in this study are secondary data obtained from the IDX. The sample in this study are property and real estate companies listed on the Indonesia Stock Exchange in 2008-2018. Data collection is using documentation techniques, namely by looking at existing documents (financial reports and annual reports). The company's financial statements are obtained from the access website of the Indonesia Stock Exchange (www.idx.co.id) in the period 2008-2018.2018. The results of the study are the company's profitability has a significant effect on the business value of property companies and real estate companies that go public on the Indonesia Stock Exchange (IDX). Company solvency has a negative and significant effect on the Business Value of Property and Real Estate Companies that are Go Public on the Indonesia Stock Exchange (IDX). Simultaneously, the company's profitability and solvency affect the business value of property companies and real estate companies that go public on the Indonesia Stock Exchange (IDX).